A longitudinal study of adaption to prison after initial incarceration. (March 2019) - Kovács, Zsuzsanna; Kun, Bernadette; Griffiths, Mark D.; Demetrovics, Zsolt
Highlights: Research into moral emotions has become an area of psychiatric interest. Moral emotions among recently incarcerated prisoners were assessed longitudinally. Shame correlated positively with somatization symptoms, distraction, and self-blame. Guilt correlated positively with self-blame, negatively with venting on emotion. Initial psychological factors did not influence adaptation after four months incarceration. Abstract: Much of the psychiatric literature about prisoners concerns the associations between psychiatric conditions and criminality. More recently, there has been increased psychiatric interest in the moral emotions (i.e., emotions related to the rightness or wrongness of an individual's actions) and their association with psychological problems and psychopathology. The role of moral emotions has never previously been studied in relation to prison adaptation on initial incarceration. Their impact in adaptation to prison life was studied longitudinally. Immediately after prison incarceration, 316 adult male offenders were assessed in relation to moral emotions, coping strategies, and somatization symptoms. After four months, information relating to their prison adaptation were recorded using official data. Findings showed that (i) offence-related shame correlated positively with somatization symptoms, distraction, and self-blame, and that (ii) offence-related guilt correlated positively with self-blame, and negatively with venting on emotion. The relationship between self-blame and somatization was partly mediated by offence-related shame and guilt. Previous research has demonstrated that moral emotions are associated with increased severity of psychopathology such as depression, suicidal ideation, and psychological problems generally. Therefore, it is important that psychiatrists are aware of the effect that moral emotions can have on psychological functioning. Implications for prison psychiatrists are discussed.